Attenuated immune control of Epstein–Barr virus in humanized mice is associated with the multiple sclerosis risk factor HLA‐DR15. Issue 1 (3rd November 2020) - Zdimerova, Hana; Murer, Anita; Engelmann, Christine; Raykova, Ana; Deng, Yun; Gujer, Cornelia; Rühl, Julia; McHugh, Donal; Caduff, Nicole; Naghavian, Reza; Pezzino, Gaetana; Capaul, Riccarda; et al.
Abstract: Immune responses to Epstein–Barr virus (EBV) infection synergize with the main genetic risk factor HLA‐DRB1*15:01 (HLA‐DR15) to increase the likelihood to develop the autoimmune disease multiple sclerosis (MS) at least sevenfold. In order to gain insights into this synergy, we investigated HLA‐DR15 positive human immune compartments after reconstitution in immune‐compromised mice (humanized mice) with and without EBV infection. We detected elevated activation of both CD4 + and CD8 + T cells in HLA‐DR15 donor‐reconstituted humanized mice at steady state, even when compared to immune compartments carrying HLA‐DRB1*04:01 (HLA‐DR4), which is associated with other autoimmune diseases. Increased CD8 + T cell expansion and activation was also observed in HLA‐DR15 donor‐reconstituted humanized mice after EBV infection. Despite this higher immune activation, EBV viral loads were less well controlled in the context of HLA‐DR15. Indeed, HLA‐DR15‐restricted CD4 + T cell clones recognized EBV‐transformed B cell lines less efficiently and demonstrated cross‐reactivity toward allogeneic target cells and one MS autoantigen. These findings suggest that EBV as one of the main environmental risk factors and HLA‐DR15 as the main genetic risk factor for MS synergize by priming hyperreactive T‐cell compartments, which then control the viral infection less efficiently and contain cross‐reactive CD4 + T cell clones. Abstract : Through EBV infection of humanized mice reconstituted with human immune systems positive for the main genetic risk factor for MS HLA‐DR15, we demonstrate T‐cell hyperactivation and less efficient viral control. These results provide insights into the synergy between EBV infection and genetic predisposition for MS development.